The Impact of the Principal's Leadership Style and Work Motivation on Teacher Performance - Zarwini, Zarwini; Ahyani, Nur; Fitriani, Yessi (Journal of Social Work and Science Education, 2022)
The purpose of this study is to determine and analyze the following relationships: (1) the relationship between the principal's leadership style and teacher performance; (2) the relationship between teacher work motivation and teacher performance; and (3) the relationship between the principal's leadership style and teacher work motivation combined on teacher performance. This is a quantitative study using the partial correlation approach. This study was carried out in the State Vocational High School in Banyuasin III District, with 80 teachers serving as participants. Questionnaires and documents are used to collect data. Construction and content validity are used in the validity test. Cronbach's Alpha is used in the dependability test. The normality, homogeneity, and linearity tests were employed in the analytical precondition test, and the data were analyzed using descriptive and inferential data analysis approaches. The findings revealed a partly and concurrently favorable and substantial association between the principal's leadership style and work motivation toward teacher performance.